Insect fauna on coconut (cocos nucifera L. ) spadix and effect of pesticides on major pollinators - Shaiju Simon (Department of Agricultural Entomology, College of Agriculture, 2006)
An investigation was carried out to document the different insect species visiting the coconut inflorescence, to find out the variations in the foraging activity of different insect species and to assess the relative safety/toxicity of some commonly used pesticides to honeybees. The study revealed that the coconut inflorescence attracted thirty different species of insects towards it. These insect species visited the inflorescence to feed on either pollen or nectar or both. Bees viz., Apis dorsata, A. mellifera, A. cerana indica, Trigona iridipennis, Braunsapis sp and Eupetersia sp were found to collect both pollen and nectar of which A. mellifera and A. cerana indica dominated. Bees were found to forage on the inflorescence throughout the day and exhibit a peak period of activity during 0900 h in case of A. mellifera and A. cerana indica and during 1200 h in case of T. iridipennis. All these species of bees exhibited two distinct peaks during the day of which the second peak was during 1500 h. They mainly collected pollen from half opened male flowers. Ant species that foraged on the coconut inflorescence in large numbers were Solenopsis geminata, Myrmicaria brunnea, Dolichoderus sp, Camponotus sericeus. They visited the inflorescence for feeding pollen and nectar. The population of ants remained more or less same throughout the day, they visited in higher numbers during 0900 h. They were present on the inflorescence throughout the day and maximum during 0900 h. Other insect species that visited the palm inflorescence were flies (Bactrocera cucurbitae, B. dorsalis, Musca domestica, Hemipyrellia sp., Graptomyza brevirostris and Sarcophaga sp.), wasps (Polistes hebraeus, Chalybion bengalense, Ropalidia variegata, Vespa cincta and Vespa sp.), beetles (Oxycetonia versicolor and Oxycetonia sp.) and moths (Euchromia polymena and Melanitis leda ismene). The maximum population of insects was observed on the 13th day of the male phase and in the female phase it was on the second day. The population fluctuations recorded over a period of one year showed that the occurrence of bees were the highest followed by the population of ants. Bees exhibited a significant positive correlation with maximum temperature and negative correlation with relative humidity and rainfall. The results on the evaluation of pesticides for their safety/toxicity to different species of honeybees indicated that all the chemical pesticides were toxic to honeybees. Carbaryl 0.1 per cent was the most toxic while endosulfan 0.05 per cent was the least toxic chemical. However, both azadirachtin 0.004 per cent and neem oil garlic emulsion 2.0 per cent were the safest treatments to honeybees under laboratory conditions.